Proceedings of the 2005 European Conference on Circuit Theory and Design, 2005.
DOI: 10.1109/ecctd.2005.1523063
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of bone-conducted speech

Abstract: One method to communicate in a very high noise environment is to use bone-conducted speech. In this paper, a technique of improving the quality of bone-conducted speech is presented. The bone-conducted speech signal of a speaker is passed through a reconstruction filter designed by using the long-term spectra of the bone-conducted and normal speech signals. Properties of the normal, bone-conducted and reconstructed speech signals are investigated and it is shown that for speaker recognition, the reconstructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…As mentioned before, a BCM records signals through bone vibrations and is thus less sensitive to air background noise in comparison with an ACM. However, the BCM-recorded speech signals often suffer from a loss of high acoustic-frequency components, and this issue was addressed and partially alleviated through the BCM-to-ACM conversion technique applied in tasks [18,19].…”
Section: Bcm/acm Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned before, a BCM records signals through bone vibrations and is thus less sensitive to air background noise in comparison with an ACM. However, the BCM-recorded speech signals often suffer from a loss of high acoustic-frequency components, and this issue was addressed and partially alleviated through the BCM-to-ACM conversion technique applied in tasks [18,19].…”
Section: Bcm/acm Conversionmentioning
confidence: 99%
“…al. [18] used a reconstruction filter, which is designed using the long-term spectra of the speech, to perform the conversion. Meanwhile, numerous approaches have been proposed to combine ACM-and BCM-recorded sound in hardware devices with a linear transformation for SE and speech recognition tasks [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…According to Shimamura et al [2], by passing speaker output of bone conducted speech signal a long term spectra reconstructed filter design, the arena of bone conducted and reconstructed speech from normal signal could be highly utilized. By passing normal speech signal through linear process with a transfer function of bone conduction can be obtained, to identify the properties of numerous sounds, spectral shapes by removing the dissimilarities.…”
Section: Brief Review On Approachesmentioning
confidence: 99%
“…As a speaker-dependent technique, the use of an air-and bone-conduction integrated microphone is suggested in [6]. In [7], it is reported that the quality of bone-conducted speech can be improved by utilizing both longterm spectra of the normal and bone-conducted speech signals.…”
Section: Introductionmentioning
confidence: 99%